2019
DOI: 10.2147/ott.s210697
|View full text |Cite|
|
Sign up to set email alerts
|

<p>The Long Non-Coding RNA SBF2-AS1 Exerts Oncogenic Functions In Gastric Cancer By Targeting The miR-302b-3p/E2F Transcription Factor 3 Axis</p>

Abstract: Background and aimsStudies show that the long non-coding RNA, SBF2-AS1, plays a critical role in cancer progression, but the role of SBF2-AS1 in gastric cancer has not been reported. Therefore, this study aimed to elucidate the mechanism of SBF2-AS1 in gastric cancer (GC).MethodsA meta-analysis, based on the gene expression omnibus database and TCGA dataset was performed to explore the prognostic value of SBF2-AS1 in GC. RT-PCR was also conducted to investigate the clinicopathologic value of SBF2-AS1 in GC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…However, the expression level and biological role of SBF2-AS1 in GC remains largely unclear. In the present study, we examined the expression levels of SBF2-AS1 in GC tissues and cell lines and found that the expression of SBF2-AS1 was upregulated in GC tissues and cell lines compared with adjacent normal tissues and normal gastric epithelial cell line GES1, which BioMed Research International was consistent with previous result [15]. In particular, patients with advanced TNM stages or distant metastasis had a high expression of SBF2-AS1.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the expression level and biological role of SBF2-AS1 in GC remains largely unclear. In the present study, we examined the expression levels of SBF2-AS1 in GC tissues and cell lines and found that the expression of SBF2-AS1 was upregulated in GC tissues and cell lines compared with adjacent normal tissues and normal gastric epithelial cell line GES1, which BioMed Research International was consistent with previous result [15]. In particular, patients with advanced TNM stages or distant metastasis had a high expression of SBF2-AS1.…”
Section: Discussionsupporting
confidence: 89%
“…SBF2 antisense RNA 1 (SBF2-AS1), located at the 11p15.1 locus, has been shown to play critical roles in tumor progression and function as an oncogene in several types of cancers, such as nonsmall lung cancer, cervical cancer, glioblastoma, colorectal cancer, esophageal squamous cell carcinoma, and hepatocellular carcinoma [9][10][11][12][13][14]. Although a study showed that SBF2-AS1 expression was upregulated in GC tissues [15], the roles and underlying mechanisms of SBF2-AS1 in GC remain largely unknown and need investigation. To this end, the aims of this study were to examine the expression and functional role of SBF2-AS1 in the progression and development of GC and to identify the molecular mechanism of SBF2-AS1 involved in GC progression.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that miRNAs bind to mRNAs to regulate tumorigenesis. According to previous studies, miR-432-5p could target and regulate E2F3, playing an important role in breast cancer [22], nasopharyngeal cancer [23], osteosarcoma [24], melanoma [25], and gastric cancer [26]. We also found that 1miR-432-5p sponged and negatively regulated E2F3 in PC cells.…”
Section: Discussionsupporting
confidence: 51%
“…Many studies have reported that lncRNAs combine competitively with miRNA binding sites to control gene expression [ 22 24 ]. Previous studies demonstrated that GAS5 may interact with miRNA to reduce protein expression [ 25 – 28 ].…”
Section: Resultsmentioning
confidence: 99%